Supporting people living with dementia in black, Asian and minority ethnic communities : key issues and strategies for change - Truswell, David (Jessica Kingsley Publishers, 2020)
"Focusing on individual Black, Asian and Minority Ethnic (BAME) communities such as Irish, Caribbean, South Asian, Chinese and Jewish, this accessible guide brings together key information on the impact of living with dementia in BAME communities into a single comprehensive resource for front-line staff as well as an information source for families and carers. The book sets out personal case studies and examines how to provide bespoke support and information to raise awareness and lower levels of stigma. With diagnoses among minority communities set to increase, this much-needed handbook is the perfect companion for care home workers, social workers, doctors and nurses who may lack experience in communicating with and caring for people from BAME backgrounds. It is also a valuable resource for family carers and those living with dementia"--